1999
DOI: 10.1152/ajprenal.1999.277.6.f926
|View full text |Cite
|
Sign up to set email alerts
|

Afferent arteriolar adenosine A2a receptors are coupled to KATP in in vitro perfused hydronephrotic rat kidney

Abstract: Adenosine is known to exert dual actions on the afferent arteriole, eliciting vasoconstriction, by activating A1 receptors, and vasodilation at higher concentrations, by activating lower-affinity A2 receptors. We could demonstrate both of these known adenosine responses in the in vitro perfused hydronephrotic rat kidney. Thus, 1.0 microM adenosine elicited a transient vasoconstriction blocked by 8-cyclopentyl-1,3-dipropylxanthine (DPCPX), and 10-30 microM adenosine reversed KCl-induced vasoconstriction. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 14 publications
4
49
1
Order By: Relevance
“…These results are consistent with in vitro observations that adenosine dilates renal microvasculature in the presence of the adenosine A 1 receptor antagonists (Nishiyama et al, 2001a). Recent studies also have shown that afferent (Tang et al, 1999;Nishiyama et al, 2001a) and efferent (Nishiyama et al, 2001a) arteriolar vasodilatory responses to adenosine during adenosine A 1 receptor blockade were significantly attenuated by adenosine A 2a receptor inhibition. Thus, these data as well as the results from the present study support the concept that adenosine A 2 receptor-mediated vasodilation may buffer adenosine A 1 receptor-mediated vasoconstriction in the kidney.…”
Section: Discussionsupporting
confidence: 90%
“…These results are consistent with in vitro observations that adenosine dilates renal microvasculature in the presence of the adenosine A 1 receptor antagonists (Nishiyama et al, 2001a). Recent studies also have shown that afferent (Tang et al, 1999;Nishiyama et al, 2001a) and efferent (Nishiyama et al, 2001a) arteriolar vasodilatory responses to adenosine during adenosine A 1 receptor blockade were significantly attenuated by adenosine A 2a receptor inhibition. Thus, these data as well as the results from the present study support the concept that adenosine A 2 receptor-mediated vasodilation may buffer adenosine A 1 receptor-mediated vasoconstriction in the kidney.…”
Section: Discussionsupporting
confidence: 90%
“…With the use of adenosine agonists and antagonists with different receptor subtype specificity, the data supported the concept that activation of adenosine A 1 receptors leads to constriction mainly of afferent arterioles near the glomerulus, whereas adenosine A 2 receptor activation leads to dilation mainly of the postglomerular arteries (65,90,133). Another study in the isolated perfused hydronephrotic rat kidney preparation provided evidence for both adenosine-induced constriction and dilation of afferent arterioles, and these effects were dependent on activation of adenosine A 1 and A 2a /A 2b receptors, respectively (327).…”
Section: Adenosine Effects On Pre-and Postglomerular Arteriessupporting
confidence: 57%
“…Similarly, studies in the isolated perfused rat kidney indicated a pertussis toxin-sensitive step between the occupation of adenosine A 1 receptors on renal vascular smooth muscle cells and vasoconstriction induced by increased Ca 2ϩ influx through potentialoperated Ca 2ϩ channels (286). With regard to adenosineinduced renal vasodilation, a study using an isolatedperfused hydronephrotic rat kidney preparation showed that adenosine-induced dilation of afferent arterioles was mediated by adenosine A 2a receptor-dependent activation of K ATP channels (327). A recent study in mice using intravenous infusion of adenosine indicated that the resulting renal vasodilation is due to adenosine A 2a receptor-mediated activation of endothelial NO synthase (109).…”
Section: Mechanisms Of Adenosine-mediated Vasoconstriction and Vasmentioning
confidence: 99%
“…Recently, enhancement of pressure-dependent dilatation by a reduction in extracellular adenosine has been observed in the isolated hydronephrotic kidney preparation (21). Because this preparation is devoid of TGF, the authors concluded that adenosine inhibits myogenic vasoconstriction by activating high-affinity A2aAR.…”
Section: Discussionmentioning
confidence: 99%